2017
DOI: 10.5897/ajar2016.11652
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cassava starch-alginate based coatings added with ascorbic acid and elicitor on quality and sensory attributes during pineapple storage

Abstract: Pineapple is a tropical fruit of great consume demand. However, due to its high perishability at room conditions, there is noticeable loss of quality postharvest in a short period. In this context, the use of biodegradable coatings is a promising alternative for maintaining postharvest quality. Thus, the aim of this study was to evaluate the use of cassava starch-alginate based biodegradable coatings added with ascorbic acid and an elicitor on postharvest quality and conservation of 'Pérola' pineapple. Fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…In contrast to mangaba in this experiment, in pears Villalobos-Acuña et al (2010), reported that the application of 1-MCP did not influence SS or starch hydrolysis, which, in some fruits and vegetables, is responsible for the increase in soluble solids (Azerêdo et al, 2016;Guimarães et al,2017). Santos et al (2009) also observed a tendency of TA increase in mangaba of similar maturity during storage at RA.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In contrast to mangaba in this experiment, in pears Villalobos-Acuña et al (2010), reported that the application of 1-MCP did not influence SS or starch hydrolysis, which, in some fruits and vegetables, is responsible for the increase in soluble solids (Azerêdo et al, 2016;Guimarães et al,2017). Santos et al (2009) also observed a tendency of TA increase in mangaba of similar maturity during storage at RA.…”
Section: Discussioncontrasting
confidence: 49%
“…Studies on storage of fruit under room conditions are necessary, since, in Brazil, almost all fruit is sold, at the retail level, without refrigeration (Carnelossi et al, 2009). Maintaining postharvest quality, in turn, is related to minimizing the rate of deterioration, in order to keep the product attractive to consumers for a longer period (Guimarães et al, 2017). Modified atmosphere (MA) has proven to be effective in reducing metabolic rates and extending the useful life of mangaba (Soares Júnior et al, 2008;Santos et al, 2009;Lima et al, 2015c).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, pineapples treated with 35 IP showed a peak in POD activity in the third storage period, although they showed the lowest the study conditions, which implies that the application of PEF maintains fruit metabolic rate and quality. SS are often used as an indicator of pineapple quality and ripeness level (DANTAS et al, 2015), requiring a minimum threshold of 12% for consumer acceptance of pineapple (GUIMARÃES et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Brazil has stood out as the second largest pineapple producer in the world with production of 2,694,555 ton/ha in a production area of 68,699 ha; the Northeast region is responsible for 40% of production and yield (FAO, 2021), and the state of Paraíba is currently the second largest producer in the country (IBGE, 2020), with 'Pérola' pineapple being the main cultivar (DANTAS et al, 2015). Growing production opens up challenges to reach competitive export markets, demanding development of technologies which ensure maintenance of high quality standards (GUIMARÃES et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…), jackfruit (Artocarpus heterophyllus Lam.) seeds and mango (Mangifera indica L.) kernels are considered potential sources of this polysaccharide (Falade & Ayetigbo, 2015;Guimarães et al, 2017;Madruga et al, 2014;Torres-León et al, 2018).…”
Section: Introductionmentioning
confidence: 99%